Child Language Data Exchange System Tools for Clinical Analysis - MacWhinney, Brian; Fromm, Davida (Seminars in Speech and Language, 2016)
The Child Language Data Exchange System Project has developed methods for analyzing many aspects of child language development, including grammar, lexicon, discourse, gesture, phonology, and fluency. This article will describe the methods available for each of these six fields, and how they can be used for assessment in the clinical setting.
Keywords: Databases; production; gesture; lexicon; syntax